The Pathogenesis and Diagnosis of Bile Reflux Gastropathy - Ruswhandi Martamala; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2001)
Bile reflux gastropathy is a disease caused by reflux of duodenal fluid to the gaster. This fluid contains pancreatic juices and duodenal secretion. The manifestations that occur depend on the frequency, amount, and duration of reflux. This disorder is quite rarely recognized in daily clinical practice. Endoscopy of the upper gastrointestinal tract is required to establish the diagnosis of this disorder. This paper will give a brief view of the pathogenesis and diagnostic method for this disorder. Keywords: gastropathy, bile reflux, motility